Comparison of the Antibacterial Activity of Nine Cephalosporins Against Enterobacteriaceae and Nonfermentative Gram-Negative Bacilli - Verbist, Ludo (1976)
The in vitro antibacterial activity of nine cephalosporins (cephalothin, cephaloridine, cephalexin, cefazolin, cefamandole, cefuroxime, cefatrizine, cefoxitin, and cefazaflur) was determined against 344 strains of Enterobacteriaceae and 99 nonfermentative gram-negative bacilli. Cefamandole, cefazaflur, and cefuroxime were the most active cephalosporins against the Enterobacteriaceae (with the exception of Serratia marcescens). However, cefoxitin was the only cephalosporin that inhibited all 30 S. marcescens strains in a concentration of 16 μg/ml and was by far the most active compound against selected cephalothin-resistant strains of Escherichia coli, Klebsiella, and Proteus mirabilis. Acinetobacter spp. were inhibited best by cefuroxime, but none of the cephalosporins had appreciable activity against the Pseudomonas spp.